(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT This research aims to know the exegetical questions that Al-Taher Bin Ashour (may Allah have mercy on him) mentioned in his interpretation of Surat Al-Fatihah and he answered them through collecting and studying it, which he mentioned in a manner (if you say ... I say) like those who preceded him of commentators and linguists. In this way, scientists initiate the important issues by following this way in order to find solutions to the inquiries and misconceptions of a group of people during their attempt to contemplate the verses and understand them. Scientists stimulate the minds of the listener and the reader, and they are exposed to difficult issues that are of interest to them, which prompted me to stand on them , them and know the purpose of their presentation, . I ask Allah for help And good luck.